SMALL MICRO BUSINESS DEVELOPMENT STRATEGY CV. ENAM PUTRI OF JAKARTA - Mudatsir Najamuddin; Zulmanery Manir; Wirawan Ahmad Destama (AGRIBUSINESS JOURNAL, 2020)
This research is backgrounded by the number of micros, small, and medium industries (MSMEs) increasing every year causing business competition to be more competitive. Most of the new MSME players will take some portion of the market share of old business actors which causes a reduction in the income received.  CV. Enam Putri, which is one of the pilot of MSMEs in the DKI Jakarta area, has several problems in carrying out its production.  Problems faced by CV.  Enam Putri is a year-over-year decline in production caused by increasingly fierce competition. This study aims to, identify the factors of the internal environment and external environment contained in the CV. Enam Putri, analyze the alternative strategies applied, as well as determine the priorities of the strategies to be applied.            Asa result of this study, it is known that there are seven strengths and three weaknesses as well as five opportunities and five threats identified in the CV. Enam Putri.  The SWOT matrix produces seven alternatives that can be applied by companies with two of them being priority strategies that are recommendations to be implemented, namely: maintaining product quality and service, as well as expanding cooperation with distributors.             The conclusions of this study show that based on the analysis of the SWOT matrix, the company came up with seven alternative strategies.  Based on the QSPM matrix, the priority strategy that the company will implement is the strategy of maintaining the quality and production services offered and expanding cooperation with distributors.